Design thinking framework of pervasive game to promote fitness among older adults in China - Kai, Liu (2023)
This study aims to develop and validate a design thinking framework for using pervasive games as a creative branding strategy on fitness among older adults in China. A provisional framework called GISE-B was developed through a systematic literature review to examine the relationship between game design and three domains of design thinking, i.e. interactive design, service design and experience design. A bespoke pervasive game titled Agoing was designed, developed and validated for use in this study to examine the behavioural intention (BI) of older adults, specifically to engage in fitness exercises. As an instance of the GISE-B framework of design thinking, the game was tested by adapting the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The adapted version of UTAUT was named as the UTAUT-LK model, which consists of five independent variables: performance expectancy, effort expectancy, facilitating condition, social influence and hedonic motivation. A singlegroup pretest / posttest quasi-experiment was conducted with 378 participants using a 20-item questionnaire. Collected data were analysed using SPSS and AMOS, where nonparametric statistics and structural equation model (SEM) were run to test five hypotheses. After modifying the SEM, effort expectancy (EE, b = 0.410, p = 0.033), social influence (SI, b = 0.500, p = 0.029), and hedonic motivation (HM, b = 0.539, p < 0.001) significantly and positively affect behavioural intention, whilst the effect size of the UTAUT-LK model exceeds 80% (R2 = 0.827). In conclusion, this demonstrates that with good design, older adults behavioural intention toward pervasive games enhances significantly. Furthermore, the researcher proposed the Seven Guiding Principles of pervasive game design for older adult players. This study implies that a pervasive game designed and developed using the GISE-B design thinking framework can enhance older adults intention to play the game and help them with fitness.